System Innovation on Purpose - and Leadbeater, Charles; Winhall, Jennie (The Rockwool Foundation, 2021)
In Building Better Systems, we introduced four keys to unlock system innovation: purpose and power, relationships and resource flows. These four keys make up a set. Systems are often hard to change because power, relationships, and resource flows are locked together in a reinforcing pattern to serve the system’s current purpose. Systems start to change fundamentally when this pattern is disrupted and opened up. Then a new configuration can emerge, serving a new purpose. In this essay series we delve deeper into these four keys and provide practical advice on how they can be put to use. This essay is about the role that purpose plays in orchestrating complex systems and how system innovators can create a new system around a new sense of purpose.